The Role of Bone Morphogenetic Protein 4 in Microglial Polarization in the Process of Neuropathic Pain - Liu C; Sun Q; Xu J; Shen W; Li H; Yang L (Dove Medical Press, 2022)
Changqing Liu,1,2,* Qi Sun,1,2,* Junmei Xu,1,2 Weiyun Shen,1,2 Hui Li,1,2 Lin Yang1,2 1Department of Anesthesiology, Second Xiangya Hospital, Central South University, Changsha, Hunan Province, People's Republic of China; 2Hunan Province Center for Clinical Anesthesia and Anesthesiology, Research Institute of Central South University, Changsha, People's Republic of China*These authors contributed equally to this workCorrespondence: Hui Li, Department of Anesthesiology, Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China, Fax +86 85295970, Email lihui_1166@csu.edu.cn Lin Yang, Department of Anesthesiology, Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China, Fax +86 85295970, Email linyang@csu.edu.cnBackground: Neuropathic pain (NP) is known to be highly correlated with microglial polarization, of which the regulatory mechanism remains to be elucidated. Here, the aim of this study is to further investigate the relationship between bone morphogenetic protein 4 (BMP4) and microglial polarization in the process of NP.Methods: Firstly, normal adult rats received intrathecal BMP4 administration to assess BMP4ʹs effect on microglial polarization. Secondly, a BMP4 antagonist - Noggin - was applied to a rat NP model achieved by L5 spinal nerve ligation (SNL) to investigate whether antagonizing BMP4 signaling could alleviate allodynia by reversing the imbalance of the M1/M2 polarization ratio. In both experiments, Von-Frey filaments were used to test the changes in the paw withdrawal threshold (PWT), and Western blotting, immuno-fluorescence, PCR and flow cytometry were further performed to investigate microglial activity and the expression patterns of M1 and M2 markers, respectively.Results: Firstly, BMP4 administration induced a significant PWT decrease and microglial activation in normal rats; Western blotting, PCR and flow cytometry further revealed that M1 markers including CD16, MHCII, and TNF-α showed a marked elevation after BMP4 application; while M2 markers, such as Arg-1, CD204 and IL-4, peaked at an early stage (P1 or P4) and then fell to the Sham level on P7, leading to a persistent imbalance of the M1/M2 ratio throughout the 1st week. Secondly, Noggin treatment significantly relieved allodynia and microglial activation in SNL rats. Moreover, Noggin persistently downregulated the M1 marker levels and simultaneously induced a late-stage elevation of M2 markers expressions, thereby reversing the imbalance of the M1/M2 polarization ratio.Conclusion: Our results indicate that BMP4 has the ability to induce microglial polarization. Antagonizing BMP4 signaling can relieve pain behavior via mitigating microglial activation and reversing the imbalance of the M1/M2 polarization ratio in the process of NP.Keywords: bone morphogenetic protein-4, Noggin, microglia, polarization, neuropathic pain